Comparative Performance Analysis & Modeling Of Tool Wear In Drilling - Chin, Chee Wen; Lee, Tian Soon; Subramonian, Sivarao (Oficyna Wydawnicza Uniwersytetu Zielonogórskiego, 2004)
To date, process supervision or monitoring is mainly performed by limit value checking of some measurable variables. In high automated machine tool faults like tool breakage often cause long outage times and high cost. Drill holes are one of the most common manufacturing features specified on process plans. Because holes are drilled in finished products, the rejections parts due to poor hole quality can be very expensive. It was estimate that 60% for all parts rejections due to poor hole quality. On the other hand, a work piece must often be remachined or completely rejected when the tool has failed.